Lembar Kerja Siswa Berbasis ICT Sebagai Solusi Kegiatan Latihan Pembelajaran Mandiri - Imania, Kuntum An Nisa (Petik: Jurnal Pendidikan Teknologi Informasi Dan Komunikasi, 2016)
Abstract – The main problem in this paper is focused on the use of ICT based on students’ worksheet as a solution in learning activities. The achievement of students’ learning outcomes is not easy to be solved the main problem (the root of the problem). One of which is to train students with exercises, then a collection of exercises is widely used by educators (teachers) in the form of print media or hard copy called LKS, but unfortunately sometimes the presence of LKS is generally only a set of questions that monotony which often lead to boredom, so that students become lazy in working the exercises. Sometimes the serving method of students’ worksheet also monotonous and less varied. The student worksheet that contains questions of subjects may be categorized as subjects less desirable by the students such as, math, English or science. If the serving method of students’ worksheet are not accompanied by variations, the students will get bored and unwilling to understand the questions. With the presence of LKS based ICT can address all the needs of students and teachers in implementing the learning activities to be more variety, innovative and able to enhance students' creativity. In addition, in the terms of time it is more flexible, because of the presence of ICT-based worksheets students are able to do the exercises wherever they are, as long as they were able to connect with the Internet network and can access it. The model of ICT based on interactive of the collection of exercises (LKS) is different from the collection of exercises (LKS) circulated in the schools. This LKS based on ICT interactive worksheets are used to deliver the material into a series of questions as an introduction to learners in constructing their understanding. The series of questions to each other are interconnected. So that students have to learn the use of these worksheets in a coherent from beginning to end of materials. The learners learn the material presented through questioning so that the formula or concept was found by the learners. Keywords – ICT, Students’ Worksheet, Learning, Learning Achievement